Climate-informed priorities for One CGIAR Regional Integrated Initiatives - Jarvis, Andy; Rosenstock, Todd S.; Koo, Jawoo; Thornton, Philip K.; Loboguerrero Rodriguez, Ana María; Govaerts, Bram; Ramírez Villegas, Julián Armando; Prager, Steven D.; Ghosh, Aniruddha; Fuglie, Keith (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
This report summarizes a rapid assessment of climate-related challenges to food-, land- and water- systems across the six CGIAR regions. Based on the evidence, priority geographies and systems are proposed which provide a starting point for the Regional Initiatives design process. It then assesses the readiness of the Two Degree Initiative (2DI) regional challenges for their fit to the challenges, and potential to form the basis for developing the first batch of Regional Integrated Initiatives.